Impact of pollution on microbiological dynamics in the pistil stigmas of Orobanche lutea flowers (Orobanchaceae) - Karolina Wiśniewska; Sebastian Wojciech Przemieniecki; Krzysztof Krawczyk; Anna Hoffmann; Renata Piwowarczyk (Scientific Reports)
Abstract Our understanding of the basic relationships of microbiota associated with flowers is still quite limited, especially regarding parasitic plant species. The transient nature of flower parts such as pistil stigmas provides a unique opportunity for temporal investigations. This is the first report of the analysis of bacterial and fungal communities associated with the pistil stigmas of the lucerne parasite, Orobanche lutea. We compared the microorganism communities at different developmental stages and assessed the impact of pollution at the sampling sites. We also examined the plant growth properties (PGP) of bacteria in a culture-dependent analysis. The predominant colonizers of the pistil stigmas were Proteobacteria (99.25%), with Enterobacteriaceae (49.88%) and Pseudomonadaceae (48.28%) being the major families. The prevalent fungal phylum was Basidiomycota (71.64%), with Filobasidiales (33.14%) and Tremellales (27.27%) as dominant orders. Microbial populations in polluted area showed increased bacterial and fungal diversity. Mature stigmas exhibited greater microbial variety compared to immature ones. We found higher fungal than bacteria abundance at both polluted and unpolluted sites. In culture-dependent analysis, immature stigmas from unpolluted area had the least bacterial morphotypes. Identified culturable bacteria represented the Acinetobacter, Erwinia, Micrococcus, Oceanobacillus, Pantoea, Pseudomonas, Serratia, and Staphylococcus genera. The assessment of PGP traits revealed multiple strains with plant growth-promoting potential. Microbial composition varied between polluted and unpolluted sites and was influenced by the flower’s developmental stage.